Treatment of Oily Wastewater From Port Waste Reception Facilities by Electrocoagulation - Sekman, E.; Top, S.; Uslu, E.; Varank, G.; Bilgili, M. S. (SPRINGER INTERNATIONAL PUBLISHING AG, 2011)
The present study investigated oil/water demulsification and treatment of oily wastewater originated from port waste reception facilities by electro coagulation using aluminum electrodes in a batch reactor. The efficiency of Al electrodes in removing SS, COD, and oil & grease from wastewater with different current densities and operational times were investigated. The characteristics of the wastewater vary in a wide range e.g. SS 13.3-660 mg/L, COD 240-2783 mg/L, and oil & grease 6.5-736 mg/L. The results of the study indicated that the SS, COD, and oil & grease can be removed effectively by EC process using Al electrodes. The optimum EC time and current density for SS removal (98.8%) was determined as 5 min and 16 mA/cm2, respectively. The first 5 min of the EC process give a considerable removal of COD for all current intensities (61-90%). The optimal current density for COD removal was determined as 12 mA/cm2 with the EC time of 20 min. Results indicated that oil & grease removal reached to a rate higher than 80% after EC time of 10 min for all current densities. The results demonstrated the applicability of electrocoagulation as a possible and reliable technique for the treatment of wastewater of port waste reception facilities.
Keywords: Electrocoagulation; Waste reception facility; Oily wastewater; Al electrode; BILGE WATER; REMOVAL; MEMBRANE; ULTRAFILTRATION; PURIFICATION; WASTEWATERS; Environmental Sciences & Ecology